BIRD DIVERSITY ON RECLAIMED NICKEL MINE-LAND IN KOLAKA DISTRICT SOUTHEAST SULAWESI - Toto Gunarto; Yeni Mulyani; Siti Badriyah Rushayati; Agus Priyono Kartono (Media Konservasi, 2021)
Nickel mining is one of open type mining having a high risk on environment. Birds are often used as indicators of habitat change in reclaimed mine-land. The objectives of this study were (1) to identify bird species; (2) to compare bird communities; (3) to predict biotic and abiotic factors that affect bird communities in mining reclamation land according to the age of reclamation, and natural forest in nickel mining area. This research was conducted on reclaimed land in 2006, 2007, 2008, 2009. The composition of bird species is described based on family, endemicity and feeding guild. Bird data were analyzed using Shannon index, Jacknife index, and Sorensen community similarity. Estimation of environmental factors is calculated using multiple regression analysis. This study discovered 41 bird species from 23 family classified into 7 guilds. There were 17 Sulawesi endemic species, and one of them is categorized as vulnerable by IUCN (Rhabdotorrhinus exarhatus). The highest species richness and diversity was found in year 2006 reclamation land (34 species, S = 44, H '= 3,08). The highest similarity analysis of bird communities was in 2006 reclaimed land and natural forest (Cn = 0,79). Based on the results of multiple regression analysis, 3 variables significantly affect the presence of birds (the insect abundance, number of tree species, and the closest perpendicular distance to the river). The presence of birds is influenced by food sources (insects, fruit) and the presence of water. The composition of bird species approached natural conditions with increasing age of reclaimed land. Key words: bird, community, diversity, mine, reclamation